Spatiotemporal thermal variation drives diversity trends in experimental landscapes. Issue 2 (15th December 2022) - Wolfe, Ellie; Cerini, Francesco; Besson, Marc; O'Brien, Duncan; Clements, Christopher F.
Abstract: Temperature is a fundamental driver of species' vital rates and thus coexistence, extinctions and community composition. While temperature is neither static in space nor in time, little work has incorporated spatiotemporal dynamics into community‐level investigations of thermal variation. We conducted a microcosm experiment using ciliate protozoa to test the effects of temperatures fluctuating synchronously or asynchronously on communities in two‐patch landscapes connected by short or long corridors. We monitored the abundance of each species for 4 weeks—equivalent to ~28 generations—measuring the effects of four temperature regimes and two corridor lengths on community diversity and composition. While corridor length significantly altered the trajectory of diversity change in the communities, this did not result in different community structures at the end of the experiment. The type of thermal variation significantly affected both the temporal dynamics of diversity change and final community composition, with synchronous fluctuation causing deterministic extinctions that were consistent across replicates and spatial variation causing the greatest diversity declines. Our results suggest that the presence and type of thermal variation can play an important role in structuring ecological communities, especially when it interacts with dispersal between habitat patches. Abstract : Temperature variability is increasing due to global climate change, but limited work has investigated the effects at the metacommunity level. This study uses a multiple trophic level experimental system to demonstrate that the type of thermal variation—spatial, temporal, or both—influences diversity trends and community composition through time.